Cronkhite-Canada Syndrome- The first case from Pakistan: a case report - Hassan Tanvir Ramzi; Zainab , Yumna; Sana Manzoor; Malik, Akram (Journal of the Pakistan Medical Association, 2023)
Chronkhite-Canada Syndrome is characterised by diffuse gastrointestinal polyposis, dystrophic changes of the fingernails, cutaneous hyperpigmentation, alopecia, diarrhoea, weight loss, and abdominal pain. This disease is also associated with peripheral neuropathies and autoimmune disorders. Its association with other diseases may cause the polyps to turn into malignant tumours and worsen the condition. The first-line treatment is a combination of prednisone and mesalamine. NSAIDs and antibiotic administration is based on the symptoms and needs of patients. Here, we describe a 51-year-old male who presented to us with abdominal pain and significant weight loss. His physical examination showed dystrophic nails, alopecia and hyperpigmentation. Endoscopy and colonoscopy showed multiple polyps. His manifestations were consistent with Cronkhite-Canada syndrome. We prescribed oral corticosteroids, which improved his condition. Keywords: Cronkhite-Canada syndrome, CCS, polyps, Pakistan.